Optimalisasi Gerakan Masyarakat Hidup Sehat (GERMAS) Melalui Sosialisasi Perilaku Hidup Bersih Dan Sehat (PHBS) Bagi Masyarakat - Loggar Bhilawa; Dian Anita Nuswantara; Dewi Prastiwi; Aisyaturrahmi Aisyaturrahmi (Abimanyu : Jornal of Community Engagement, 2021)
The Government of the Republic of Indonesia has issued Presidential Decree of the Republic of Indonesia number 11 of 2020 concerning the Determination of the 2019 Corona Virus Disease Public Health Emergency (COVID-19). In this Presidential Decree, the President designated Corona Virus Disease 2019 (COVID-19) as a type of disease that causes a Public Health Emergency. As well as establishing a Public Health Emergency for Corona Virus Disease 2019 (COVID-l9) in Indonesia, which must be made in accordance with the provisions of laws and regulations. In addition to issuing Presidential Decree number 11 of 2020, the government also issued Government Regulation 21/2020 concerning Large-Scale Social Restrictions in the context of Accelerating the Management of Corona Virus Disease (COVID-19). PP 21 of 2020 concerning Large-Scale Social Restrictions in the context of the Acceleration of Handling of Corona Virus Disease (COVID-19) regulates the Implementation of Large-Scale Social Restrictions stipulated by the Minister of Health and can be carried out by the Regional Government based on the approval of the Minister of Health. One of the efforts to maintain health is by applying personal hygiene so as not to become a carrier of the virus for other people. Based on WHO recommendations as well as the Surabaya City PSBB, residents are asked to implement PHBS according to WHO recommendations. This PKM is more functioned to provide information back to the public regarding PHBS efforts in accordance with WHO recommendations for maintaining personal health. It is hoped that with the implementation of this activity, the residents of the orphanage will be more aware of personal hygiene and also apply health protocols in their daily lives so that they can break the chain of transmission of Covid 19.